A comprehensive review of the use and understanding of airway pressure release ventilation. (3rd March 2020) - Mallory, Palen; Cheifetz, Ira
ABSTRACT: Introduction : Airway pressure release ventilation (APRV) is a mode of ventilation typically utilized as a rescue or alternative mode for patients with acute respiratory distress syndrome (ARDS) and hypoxemia that is refractory to conventional mechanical ventilation. APRV's indication and efficacy continue to remain unclear given lack of consensus amongst practitioners, inconsistent methodology for its use, and scarcity of convincing evidence. Areas covered : This review discusses the history of APRV, how APRV works, rationales for its use, and its theoretical advantages and disadvantages. This is followed by a review of current available literature examining APRV's use in the intensive care unit, with further focus on its use in the pediatric intensive care unit. Expert opinion : APRV is a ventilation mode with theoretical risks and benefits. Appropriate study of APRV's clinical efficacy is difficult given a heterogeneous patient population and widely variable use of APRV between centers. Despite a paucity of definitive evidence in support of either mode, it is possible that the use of APRV will begin to outpace the use of high-frequency oscillatory ventilation (HFOV) for the management of refractory hypoxemia as more attention is paid to benefits of spontaneous breathing and minimizing sedation. Furthermore, APRV's role during ECMO deserves further investigation.